Material Didáctico: Cartografía Corporal para Visibilizar la Memoria Histórica de Adultos Ciegos Víctimas del Conflicto Armado en Colombia (2023)
This undergraduate thesis aims to give visibility to the historical memory of blind adults who are victims of the armed conflict in Colombia. To achieve this, a pedagogical approach based on principles of Andragogy, Popular Education, and Dialogic Pedagogy will be implemented, using a qualitative methodology rooted in a sociocritical paradigm.